Digital technology and artificial intelligence issues in scientific works - A. N. Timokhovich; E. G. Samokhodkina; E. V. Samokhodkin; A. A. Elzon (Цифровая социология)
The article presents the results of a study to identify trends in the coverage of digital technology and artificial intelligence in scientific papers. Semantic units reflecting aspects of digitalization, artificial intelligence, augmented reality are revealed. The main semantic units, reflecting different aspects of the research field are digitalization; artificial intelligence (additional semantic units: knowledge representation, theorem proving, computer vision, robotics, machine learning, multi-agent systems, artificial intelligence tools); neural networks (additional semantic units: learning with a teacher, learning without a teacher, input data); strong or general artificial intelligence, weak or applied artificial intelligence; Marusya voice assistant, Alisa voice assistant, Siri voice assistant, Bixby voice assistant, Google Assistant; speech recognition, fingerprint recognition, human face identification. Quantitative changes in the coverage of digital technologies, artificial intelligence, augmented reality elements in scientific papers of scientists for the period from 2016 to 2021 are presented and graphically visualized. The analysis of quantitative characteristics of materials and content component of semantic units on the indicated theme is given. The subject of the study is the publications of Russian and foreign authors, dealing with the issues of digitalization and artificial intelligence, included in the database of the Russian Institute of Scientific and Technical Information of the Russian Academy of Sciences (VINITI RAS) for the period from 2016 to 2021.